2010
DOI: 10.1021/jp911116q
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Cetyltrimethylammonium Surfactant at Fused Silica/Aqueous Interfaces Studied by Vibrational Sum Frequency Generation

Abstract: Utilizing vibrational sum frequency generation (SFG), we characterized the structure of adsorbed cetyltrimethylammonium chloride (CTAC) at the silica/aqueous interface in the presence of 10 to 500 mM NaCl and as a function of surfactant surface coverage. For low ionic strengths (10 mM NaCl), results indicate that adsorbed aggregates do not change conformation with increasing surface coverage. Instead, the surfactant adsorbs as micelle-like structures at concentrations considerably lower than surface saturation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 51 publications
2
44
0
Order By: Relevance
“…A similar trend was also observed for experiments carried out at a DTAC concentration of 10 mM that will be included in a future publication that examines the SFG spectra as a function of DTAC concentration. The increase in the SFG intensity with the addition of base is consistent with a study carried out by Tyrode et al 20 at near-neutral conditions where CH resonances were not observed for CTAB adsorbed at the silica/water interface in which the lack of peaks was attributed to the centrosymmetric structure of the aggregate, as well as a later study by Hayes et al 25 carried out at pH 11 that observed CH peaks in the SFG spectra for the same surfactant and interface. The SFG spectra shown in Figure 2 indicate that the surfactant macromolecular structure at the silica/water interface becomes more non-centrosymmetric with the addition of acid or base.…”
Section: Contact Angle and Interfacial Tension Measurementssupporting
confidence: 90%
See 3 more Smart Citations
“…A similar trend was also observed for experiments carried out at a DTAC concentration of 10 mM that will be included in a future publication that examines the SFG spectra as a function of DTAC concentration. The increase in the SFG intensity with the addition of base is consistent with a study carried out by Tyrode et al 20 at near-neutral conditions where CH resonances were not observed for CTAB adsorbed at the silica/water interface in which the lack of peaks was attributed to the centrosymmetric structure of the aggregate, as well as a later study by Hayes et al 25 carried out at pH 11 that observed CH peaks in the SFG spectra for the same surfactant and interface. The SFG spectra shown in Figure 2 indicate that the surfactant macromolecular structure at the silica/water interface becomes more non-centrosymmetric with the addition of acid or base.…”
Section: Contact Angle and Interfacial Tension Measurementssupporting
confidence: 90%
“…The peak assignment was facilitated by comparing SFG spectra for DTAC and DTAB-d 25 as shown in Figure 3. For DTAB-d 25 , which 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 Focusing on the symmetric modes, the SFG spectra were fitted with Eq 4 in the range between 2750 cm -1 and 2890 cm -1 in order to determine the amplitude of these modes. The results are presented in Figure 4.…”
Section: Contact Angle and Interfacial Tension Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…Molecular-level information, obtained from both experiments and simulations, is necessary for achieving the desired understanding. Vibrational sum frequency generation (VSFG) experiments have been widely used to study water [44,45] and surfactants [46,47] at interfaces. Adsorption [48,49] and scattering experiments [22,25,26,[50][51][52][53] are performed to determine the structure of the adsorbed surfactant layers.…”
Section: Introductionmentioning
confidence: 99%